Seeking your advice - AJP, Editor (Asian Journal of Pharmaceutics (AJP), 2014)
Asian Journal of Pharmaceutics (AJP) has made a modest entry to the Index Copernicus, for the year 2008, with 4.89 points. AJP readership is up. After crossing the one hundred thousand mark early in 2009, the journal has already registered 1.5 hundred thousand viewings and is bringing some money through web advertisements.